Is Green Concept in Residential Expensive? - Denny Stevanus Widyanto; Januar Budiman; Njo Anastasia (Petra International Journal of Business Studies, 2020)
A house, especially landed housing is one of the primary needs and yet scarcity continues to occur due to the depletion of land quantity and increasingly rising selling prices. In order for the development of a residential area to be more directed and productive, it is necessary to analyze the appropriate land allocation and generate maximum land value. Through this paper, the author examines the effect of a residential planning with green concepts along with housing support facilities in relevance with highest and best use analysis, especially its impact on costs and revenues.